2016
DOI: 10.3402/jom.v8.31854
|View full text |Cite
|
Sign up to set email alerts
|

Oral, intestinal, and skin bacteria in ventral hernia mesh implants

Abstract: BackgroundIn ventral hernia surgery, mesh implants are used to reduce recurrence. Infection after mesh implantation can be a problem and rates around 6–10% have been reported. Bacterial colonization of mesh implants in patients without clinical signs of infection has not been thoroughly investigated. Molecular techniques have proven effective in demonstrating bacterial diversity in various environments and are able to identify bacteria on a gene-specific level.ObjectiveThe purpose of this study was to detect b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 37 publications
(44 reference statements)
0
18
0
Order By: Relevance
“…The authors of this work have demonstrated for the first time that hernia meshes could be reached by bacteria, not only originating from the skin and the gut of the patient, but also from oral site (due to periodontal diseases) [24]. This study suggests as well that bacterial biofilm settled on the meshes in patients without clinical signs of infection could a priori also promote recurrence [24].…”
Section: Pathogenesis Of Mesh-related Contaminationmentioning
confidence: 68%
See 2 more Smart Citations
“…The authors of this work have demonstrated for the first time that hernia meshes could be reached by bacteria, not only originating from the skin and the gut of the patient, but also from oral site (due to periodontal diseases) [24]. This study suggests as well that bacterial biofilm settled on the meshes in patients without clinical signs of infection could a priori also promote recurrence [24].…”
Section: Pathogenesis Of Mesh-related Contaminationmentioning
confidence: 68%
“…In those complicated cases, the isolation, cultivation and identification of every causative agents still remains challenging and numerous pathogens may remain underestimated depending of the exact practices in the clinical microbiology lab [16,23]. The utilization of modern biotechnological tools such as gene sequencing has been recently employed as alternative to conventional cultivation methods to analyse the microbial population of explanted mesh following hernia recurrence [24]. The authors of this work have demonstrated for the first time that hernia meshes could be reached by bacteria, not only originating from the skin and the gut of the patient, but also from oral site (due to periodontal diseases) [24].…”
Section: Pathogenesis Of Mesh-related Contaminationmentioning
confidence: 99%
See 1 more Smart Citation
“…Soaked mesh up to 15 cm in diameter can be pulled through a 5‐mm port site. A recent Norwegian publication demonstrates the association between hernia recurrence and mesh infection, suggesting that bacterial colonization of the mesh may occur in up to two thirds of those who present with recurrence . Reported rates of actual mesh infection vary between studies.…”
Section: Discussionmentioning
confidence: 99%
“…S. epidermidis, β-hemolytic Streptococcus, Enterococcus, and anaerobic bacteria are also observed in the patch infection [12].…”
Section: Bacteriological Features Of Patch Infectionmentioning
confidence: 96%